Study on the Influencing Factors of Miners’ Unsafe Behavior Propagation - You, Mengjie; Li, Shuang; Li, Dingwei; Xia, Qing (Frontiers in Psychology, 2019)
This study aims to explore the causes of unsafe behavior propagation (UBP) and then control the spread and prevalence of unsafe behavior in miners' social networks. Based on social learning theory, this study built a hypothetical model of correlation between safety atmosphere, safety knowledge, influence degree of key figures, and UBP. We administered an empirical study of an effective questionnaire from 433 miners in coal mines via structural equation modeling. The results showed that safety knowledge played a mediating role in the process of UBP influenced by safety atmosphere, and influence degree of key figures also mediated the relationship between safety knowledge and UBP. Furthermore, the relation between safety atmosphere and UBP was sequentially mediated by safety knowledge and influence degree of key figures. Our research results provided new theoretical and methodological support for interfering with miners' unsafe behavior.